Digital sensitivity of adolescents and algorithmic power: A study of communication issues and practices - AHMANE, Loubna (The International tax journal, 2026)
This study examines adolescents' digital sensitivity regarding algorithmic mechanisms that shape the digital platforms' infrastructures. It highlights the intertwined relationship between communication issues and technical dynamics, particularly how algorithms organize, prioritize, and disseminate content to which adolescents are exposed, as well as the impact of these processes on adolescents' relationship with information and their social interactions. The study emphasizes that algorithmic logic may constitute a growing vulnerability factor in a hyper-connected environment. To achieve a joint understanding of individual and institutional dimensions, a mixed methodology (quantitative and qualitative) was employed, focusing on adolescents aged 12 to 18 and based on a diversified sample in terms of gender, socio-economic status, and geographical setting (urban/rural). Accordingly, findings derived from methodological triangulation indicate that adolescents who are more sensitive or less aware of digital issues are more likely to become captive to algorithmic bubbles. These conclusions open up perspectives for the development of media education mechanisms and pathways for regulating digital platforms.